Changing Oar Rotation Axis Position Increases Catch Angle During Indoor and In-Field Para-Rowing: A Randomized Crossover Trial Verified by a Repeated Measurement Trial - Held, Steffen; Rappelt, Ludwig; Wicker, Pamela; Donath, Lars (Frontiers in Physiology, 2022)
A long rowing stroke length is crucial for adequate rowing performance. Therefore, the relocation of the oar from traditional “in front” (NORM) to “behind the rotation-axis” (GATE) may increase (para) rowing performance. Thus, 15 able-bodied rowers (21.4 ± 3.6 yrs; height: 187 ± 8 cm; 85.4 ± 8.2 kg) completed indoor TANK rowing, 2min-TimeTrials (2min-TT) of GATE and NORM in a randomized order. Subsequently, one elite Paralympic oarsman (37 yrs, 185 cm, 67 kg) performed a multiple single case in-field BOAT testing (24x2min-TT of GATE and NORM in a randomized order). GATE revealed significantly larger catch angles during TANK (p = 0.001, SMD = 0.84; +97.1 ± 120.4 %) and BOAT (p < 0.021; SMD = 2.69; +11.9 ± 3.2 %; Tau-U = 0.70) compared to NORM. While total stroke length, rowing power and work-per-stroke increased in GATE during TANK (p < 0.010, SMD > 0.634), no such significant changes of these performance parameters between GATE and NORM were observed during BOAT (p > 0.021; SMD < 0.58; Tau-U < 0.29). Rowing economy related parameters (power or speed per oxygen uptake) and boat speed also showed no significant differences between GATE und NORM during BOAT (p > 0.61; SMD < 0.31; Tau-U < 0.19). The shape of the force-angle curve (position of peak force and ratio between average and maximal force) remained unaffected from GATE during both TANK (p > 0.73, SMD < 0.1) and BOAT (p > 0.63; SMD < 0.60; Tau-U < 0.27). In conclusion, GATE shifted the entire rowing stroke towards the catch (+6.6 ± 1.8°) without notably affecting relevant performance parameters during BOAT. Particularly during crew rowing, the minimization of detrimental boat movements for perfect synchrony should be aimed for. Accordingly, the combined application of GATE and NORM (for different athletes in crew boats) may be beneficial for rowing synchronization.